Non-conventional vegetables produced in the south of Minas Gerais (Research, Society and Development, 2022)
Non-conventional food plants (NFP) represent great importance and growing productive potential, with the identification of species in each region being important. In this sense, the objective was to identify and quantify variables that characterize the different species of NFP in the southern region of Minas Gerais. A representative group sample was used with 96 producers selected from 12 associations, covering the period 2018 to 2019. 35 species of PANC produced in a total area of 138 hectares were catalogued, being Yam-Taro (Colocasia esculenta), Leek (Allium porrum), Ora-Pro-Nobis (Pereskia aculeata), Caracara (Dioscorea bulbifera), Pigeon pea (Cajanus cajan), Saffron (Curcuma longa), Ginger (Zingiber officinale), Spinach (Spinacea oleracea), Potato Yacon (Smallanthus sonchifolius), and Serralha (Sonchus oleraceus), the most representative species in the area produced (64%). The Camponesa association, from Campo do Meio-MG, represented the largest producer of unconventional food plants in the South of Minas Gerais (30% of the total NFP sold). There was an increasing trend in the number of producers over 40 years old involved with these species. The main form of commercialization adopted is direct retail sales 33%, in open fairs. In the modality of land use, there was a predominance (66%) of cultivation on own, family and organic properties.